(untitled) (International Journal of Physiotherapy, 2014)
Background: Childhood obesity has reached epidemic proportions worldwide and is associated with increased cardio vascular mortality and morbidity in adult life. In children, obesity correlates strongly with a progressive reduction in the level of physical activity and changes in food habits. Methods: This study is a qualitative research study. A secondary data collection technique was utilized and conducted through a search of articles published between 2005 and 2014 in PubMed and Google scholar databases. The objective of the present study is to provide a systemic review of the available literature and outline the factors in early life that are associated with an increased risk of obesity in children there by leading to poor gross motor skill performance with the help of Anthropometric assessment, Body composition and Motor skills proficiency. Results: Importantly recent studies have demonstrated that exercise training improves vascular endothelial function and stimulation of pressure receptors leading to increased vagal activity in obese children. The current literature highlights the importance of adding exercise programs to clinics, schools and families for the physical and psychological wellbeing of children. Conclusion: Overall findings from the present review showed that normal children with physical exercise are more superior in motor skills compared to other peers. Results of the previous studies indicated that normal children’s are more efficient in bilateral coordination in greater balancing, efficient upper limb coordination and greater strength.